Different Mechanisms Explain Decoupled Co‐Occurrence Patterns of Native and Non‐Native Macroinvertebrates - Chengzong Tian; Jorge García‐Girón; Zi Xun Kua; Xiaopei Du; Fangyuan Xiong; Alejandro Nistal‐García; Xiongdong Zhou; Wei Xin; Zhongyang Li (Global Change Biology, 2025)
Biological invasion is a key driver of biodiversity loss, leading to significant changes in community composition and structure. Hence, understanding how biological invasions influence community assembly processes is crucial for identifying invasion mechanisms and developing management strategies aimed at minimizing their impacts on natural ecosystems. Beyond environmental filtering or niche‐based exclusion, biotic interactions (e.g., interspecific competition) between invasive and their native counterparts can also affect species distributions and local invasion dynamics. This study combined joint Species Distribution Models (jSDMs) with a long‐term European‐level dataset to uncover co‐occurrence patterns and community organization of freshwater macroinvertebrates in the context of biological invasion. To do this, we considered functional traits, phylogenetic relationships, environmental niches, and residual variance potentially mirroring species‐to‐species interactions between non‐native and native species. Environmental covariates exhibited significant differences in explaining variation of occurrences between native and non‐native species; although environmental filtering had a more pronounced effect on native species. This finding supported the hypothesis that non‐native species generally exhibit broader environmental niches. Indeed, our findings emphasized the importance of biotic filtering (in the form of interspecific competition and invasion meltdown among non‐native species) acting beyond the abiotic environment in shaping the distribution of non‐native and native species, providing a more nuanced view of the key drivers underlying invasion risk and success.